2011
DOI: 10.1038/aja.2011.86
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effects and mechanisms of preoperative 5α-reductase inhibitors on intraoperative haemorrhage during surgery for benign prostatic hyperplasia

Abstract: 1 5a-reductase inhibitors (5a-RIs), including finasteride and dutasteride, are commonly used medical therapies for benign prostatic hyperplasia (BPH). Many studies reported that preoperative 5a-RI had impact on intraoperative haemorrhage during surgery for BPH, but it was still in controversial. So, we conducted a systematic review of the effects and mechanisms of 5a-RIs on intraoperative bleeding for BPH. MEDLINE, EMBASE, the Cochrane Controlled Trail Register of Controlled Trials and the reference lists of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The effect of 5ARI use on intraoperative and postoperative bleeding has been studied for standard TURP, with some studies showing a decrease in bleeding for those on 5ARIs compared to controls and other studies showing no difference. [22][23][24][25][26] However, to our knowledge no other studies have looked directly at the effect of 5ARI use on delayed hematuria, specifically after PVP. Our results suggest a role for 5ARIs in reducing post-PVP hematuria, and the utility of prospective, randomized studies to elucidate exactly what that role may be.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of 5ARI use on intraoperative and postoperative bleeding has been studied for standard TURP, with some studies showing a decrease in bleeding for those on 5ARIs compared to controls and other studies showing no difference. [22][23][24][25][26] However, to our knowledge no other studies have looked directly at the effect of 5ARI use on delayed hematuria, specifically after PVP. Our results suggest a role for 5ARIs in reducing post-PVP hematuria, and the utility of prospective, randomized studies to elucidate exactly what that role may be.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that finasteride could reduce perioperative bleeding in patients undergoing TURP [6][7][8][9][10][11][12] . However, the effect of preoperative treatment with dutasteride in reducing blood loss during TURP remains controversial [11,12] . Our meta-analysis reviewed 10 available comparative studies involving 1,022 participants (521 treated with dutasteride and 501 in the control group); it indicated that preoperative administration of dutasteide could significantly reduce the change of Hb and Hct level in TURP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, dutasteride should also be effective in reducing blood loss. Two systematic review and meta-analyses conducted by Zong et al [11] and Zhu et al [12] identified that preoperative dutasteride use could not decrease bleeding during TURP. However, only 4 studies [14][15][16][17] about dutasteride were included in their analysis and different reference values were used to classify the intraoperative blood loss.…”
mentioning
confidence: 99%
“…This feature was used to prevent blood loss related to TURP. The efficacy of dutasteride in the treatment of gross hematuria associated with BPH is well established [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%